Toward a possible trauma subtype of functional neurological disorder: impact on symptom severity and physical health - Paredes-Echeverri, Sara; Guthrie, Andrew J.; Perez, David L. (Frontiers in Psychiatry, 2022)
Background: As a group, individuals with functional neurological disorder (FND) report an approximately 3-fold increase in adverse life experiences (ALEs) compared to healthy controls. In patients with FND, studies have identified a positive correlation between symptom severity and the magnitude of ALEs. While not all individuals with FND report ALEs, such findings raise the possibility of a trauma-subtype of FND. Objective: This study investigated if patients with FND, with or without probable post-traumatic stress disorder (PTSD) and/or significant childhood maltreatment, differed in their symptom severity and physical health. Methods: 78 patients with FND were recruited (functional seizures, n=34; functional movement disorder, n=56). Participants completed self-report measures of symptom severity (Somatoform Dissociation Questionniare-20 (SDQ-20), Screening for Somatoform Disorders: Conversion Disorder subscale (SOMS:CD), Patient Health Questionniare-15 (PHQ-15)), physical health (Short Form Health Survey-36 (SF36-physical health)), childhood maltreatment (Childhood Trauma Questionnaire (CTQ)), and PTSD (PTSD Checklist-5 (PCL-5)); a psychometric battery of other common predisposing vulnerabilities was also completed. To adjust for multiple comparisons, a Bonferroni correction was applied to all univariate analyses. Results: Patients with FND and probable PTSD (n=33) vs. those without probable PTSD (n=43) had statistically significant increased scores on all symptom severity measures – as well as decreased physical health scores. In secondary post hoc regression analyses, these findings remained significant adjusting for age, sex, race, college education, and: pathological dissociation; alexithymia; attachment styles; personality characteristics; resilience scores; functional seizures subtype; or moderate-to-severe childhood abuse and neglect scores; SOMS:CD and SDQ-20 findings also held adjusting for depression and anxiety scores. In a separate set of analyses, patients with FND and moderate-to-severe childhood abuse (n=46) vs. those without moderate-to-severe childhood abuse (n=32) showed statistically significant increased SDQ-20 and PHQ-15 scores; in post hoc regressions, these findings held adjusting for demographic and other variables. Stratification by childhood neglect did not relate to symptom severity or physical health scores. Conclusions: This study provides support for a possible trauma-subtype of FND. Future research should investigate the neurobiological and treatment relevance of a FND trauma-subtype, as well as continuing to delineate clinical characteristics and mechanisms in individuals with FND that lack a history of ALEs.